Strategic Innovation and Emerging Markets: Bibliometric Analysis of Trends, Issues and Future Directions - Maulina, Erna; Taryana, Agus; Ruslan, Budiana; Arifianti, Ria; Rachmat Fauzan, Tribowo (DINASTI RESEARCH, 2024)
This study uses bibliometric analysis to investigate the complex connections between strategic innovation and emerging market. In this dynamic subject, it highlights prospective future research directions and indicates important obstacles and emerging trends. A carefully selected group of 5,467 research papers is extracted from the vast Scopus database using a custom search phrase that is intended to highlight strategic innovation and emerging markets. After a rigorous manual screening procedure that follows the PRISMA protocol, 496 studies are carefully chosen for in-depth bibliometric analysis. This study uses scientific mapping tools to visually display the complex interactions and interconnections among diverse research streams in addition to analyzing the performance of these This study uses bibliometric analysis to investigate the complex connections between strategic innovation and emerging market. In this dynamic subject, it highlights prospective future research directions and indicates important obstacles and emerging trends. A carefully selected group of 5,467 research papers is extracted from the vast Scopus database using a custom search phrase that is intended to highlight strategic innovation and emerging markets. After a rigorous manual screening procedure that follows the PRISMA protocol, 496 studies are carefully chosen for in-depth bibliometric analysis. This study uses scientific mapping tools to visually display the complex interactions and interconnections among diverse research streams in addition to analyzing the performance of these selected publications. The results highlight how important it is for firms to be ambidextrous in order to effectively handle the variety of difficulties and new opportunities that growing markets bring. The capacity to simultaneously investigate novel ideas and make use of current resources becomes essential in this dynamic environment in order to ensure long-term success. This study effectively synthesizes previous material by offering a unique viewpoint on the complex links between strategic innovation and emerging markets. It provides insightful information that advances our knowledge of how companies can successfully negotiate the challenging terrain of emerging markets and adopt strategic innovation in order to prosper in this revolutionary climate.